SOCIAL CURATION: COLLECTIVE PARTICIPATION IN THE CURATION OF DIGITAL-VIRTUAL MUSEUM ENVIRONMENTS - Jorente, Maria José Vicentini [UNESP]; Batista, Lucineia da Silva [UNESP]; Padua, Mariana Cantisani [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2022)
Objective: The objective was to study a form of Digital Curation that contemplates social participation, that is, a curation model in which the community participates in its processes, and, consequently, feels represented, with a participatory, horizontal and inclusive approach. Methods: The methodology is descriptive and exploratory, with a literature review and research on web environments and initiatives that disclose the practice of social curation. Results: In the international context, some authors have addressed the social aspect of curation through the participatory approach. However, it was not possible to identify national authors who approach this perspective in the literature. The study observed that the Museu da Pessoa is pioneer in collaborative curation. International initiatives demonstrate the openness to participatory curation, transforming the community into cultural heritage curators. Conclusions: Netizens have become co-curators of cultural memories in digital-virtual environments, and the curation can now count on the participation of the community in the reconstruction of the narratives of cultural heritage in hybrid environments. Participatory approach promotes equity in the relationship between the institution and society, democratizing access to transcultural heritage and enabling Social Curation.
Curadoria social: participação col etiva na curadoria de ambientes dígito virtuais de museus
Keywords: Design Thinking; Digital Curation; Information and Communication Technologies (ICT); Participatory Approach; Social Curation